Teaching NeuroImage: Subacute Encephalopathy With Seizures in Alcoholics (SESA)–Related Abnormalities on EEG and MRI. (23rd August 2022) - Suh, Jimmy; Chen, Denise; Albin, Catherine
Abstract : A 72-year-old woman with alcohol use disorder (last drink 1 week prior) and no seizure history was admitted with encephalopathy. Admission MRI demonstrated focal, edematous T2 FLAIR hyperintensities (Figure 1), and EEG showed abundant lateralized periodic discharges (LPDs) (Figure 2). Evaluation for other etiologies was negative. Treatment with multiple antiseizure medications (ASMs) led to significant clinical and radiographical improvement.